Utilización de estrategias mágicas para el manejo de situaciones stresantes en estudiantes Universitarios/as - Farkas, Chamarrita (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The aim of this study was to examine the use of magical strategies as a means to cope with academic stressors in a sample o Chilean college students Their incidence was analyzed, including the situation´s stress and controllability levels, sex, and locus of control Rotter´s (1990) Locus of Control Scale and vignettes designed for this study were administered. Frequency analysis indicated that 27.5% of the participants reported using magical strategies as a means to cope with academic stressors. Also there was a significant direct correlation with external attributions. Results, as well as those aspects that explain their occurrence, are discussed.